A cross population between D. kaki and D. virginiana shows high variability for saline tolerance and improved salt stress tolerance - Gil-Muñoz, Francisco; Pérez-Pérez, Juan G.; Quinones, Ana; Primo-Capella, Amparo; Cebolla-Cornejo, Jaime; Forner-Giner, María A.; Badenes, María L. (Carl Ng, University College Dublin, 2020)
Persimmon (Diospyros kaki Thunb.) production is facing important problems related to climate change in the Mediterranean areas. One of them is soil salinization caused by the decrease and change of the rainfall distribution. In this context, there is a need to develop cultivars adapted to the increasingly challenging soil conditions. In this study, a backcross between (D. kaki x D. virginiana) x D. kaki was conducted, to unravel the mechanism involved in salinity tolerance of persimmon. The backcross involved the two species most used as rootstock for persimmon production. Both species are clearly distinct in their level of tolerance to salinity. Variables related to growth, leaf gas exchange, leaf water relations and content of nutrients were significantly affected by saline stress in the backcross population. Water flow regulation appears as a mechanism of salt tolerance in persimmon via differences in water potential and transpiration rate, which reduces ion entrance in the plant. Genetic expression of eight putative orthologous genes involved in different mechanisms leading to salt tolerance was analyzed. Differences in expression levels among populations under saline or control treatment were found. The ‘High affinity potassium transporter’ (HKT1-like) reduced its expression levels in the roots in all studied populations. Results obtained allowed selection of tolerant rootstocks genotypes and describe the hypothesis about the mechanisms involved in salt tolerance in persimmon that will be useful for breeding salinity tolerant rootstocks